2018
DOI: 10.3233/jad-180201
|View full text |Cite
|
Sign up to set email alerts
|

miRNA 933 Expression by Endothelial Cells is Increased by 27-Hydroxycholesterol and is More Prevalent in Plasma from Dementia Patients

Abstract: Alzheimer’s disease (AD) etiology is complex; gene and environmental risk factors may interact to predispose to disease. From single nucleotide polymorphism analyses and genome-wide association studies, a number of candidate risk genes for the onset of AD have been identified and cluster around lipid metabolism and inflammation. We hypothesized that endothelial cells which line the blood-brain barrier are likely to be critical mediators of systemic metabolism within the brain. Therefore, we have studied the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…Increasing numbers of studies have suggested that 27‐hydroxycholesterol (27‐OHC), an oxidative metabolite of cholesterol, may cause inflammation in the brain and is associated with an increased risk of dementia including AD (Dias, Brown, Shabir, Polidori, & Griffiths, ; Testa et al, ,). Our recent studies showed the toxic effect of 27‐OHC in C6 glioma cells and in the brains of Sprague–Dawley rats fed a high‐cholesterol diet.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of studies have suggested that 27‐hydroxycholesterol (27‐OHC), an oxidative metabolite of cholesterol, may cause inflammation in the brain and is associated with an increased risk of dementia including AD (Dias, Brown, Shabir, Polidori, & Griffiths, ; Testa et al, ,). Our recent studies showed the toxic effect of 27‐OHC in C6 glioma cells and in the brains of Sprague–Dawley rats fed a high‐cholesterol diet.…”
Section: Introductionmentioning
confidence: 99%
“…AD-related alterations in the expression of miRNAs have been described by several studies and these alterations have been reported not only in disease-related brain regions but also in peripheral body fluids such as CSF (14)(15)(16)(17), blood (18), plasma (19) and serum (20). Compared to brain tissue, peripheral samples, including blood, plasma, and serum are much easier to collect and determination of miRNA expression profiles in peripheral components enables these miRNAs to be used as a source of non-invasive biomarkers in AD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, authors suggested circulating miRNA-933 as a feasible predictor for ASCVD at the early stage [31]. On the contrary, other study reported that 27-hydroxycholesterol, a cholesterol metabolite, increased the level of miRNA-933 in microvascular endothelial cells along with the elevation of TNF- α and IL-6 [32]. Given these reports together with our result, miRNA-933 may play a role in the development and/or severity of vascular diseases although the mechanism has not been established.…”
Section: Discussionmentioning
confidence: 99%